General dermatology benefits of dermoscopy (International Journal of Food and Nutritional Sciences, 2022)
Dermoscopy is helpful for assessing vascular structures that are not apparent to the naked eye as well as for improving the diagnostic precision in the clinical examination of pigmented skin lesions. Dermoscopy has subsequently been used more frequently for the differential diagnosis of non-pigmented skin conditions, such as malignancies as well as inflammatory and viral diseases. The dermoscopic characteristics of several nonpigmented tumoral and nontumoral skin lesions are reviewed in this article, along with the dermoscopic standards used to track skin reactions to various therapies.